Strategi Kreatif Pada Program Kok Bisa Viral NTV Berdasarkan Teori Creative Strategy - Ahmad Risqi; Nitasri Murawaty Girsang (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
The development of digital media has caused television programs to be required to produce relevant, engaging, and trend-oriented content in order to maintain their existence amid increasing media competition. This study aims to identify the creative strategies implemented by the creative team of the television program Kok Bisa Viral in producing up-to-date content as an effort to maintain program sustainability. This research uses a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The analysis applies Graham Wallas’ creative process theory, which consists of four stages: preparation, incubation, illumination, and verification. The results show that the creative strategies applied by the Kok Bisa Viral team in creating relevant content include theme research, content repackaging, theme branching development, program concept development, and changes in editing concepts. These strategies are carried out through idea exploration, creative discussions, adaptation to digital trends, and evaluation processes to ensure that the produced content meets audience expectations. The implementation of these creative strategies demonstrates that adaptability and innovation within the creative team play an important role in maintaining the existence of television programs amid the continuous development of the media industry.